Optimizing Counseling Guidance Facilities and Infrastructure to Support Students' Personal Growth - Adha, Idyana; Firman, Firman; Neviyarni, Neviyarni (Widyagogik, 2025)
Personal growth is a process that involves developing oneself psychologically, socially, and emotionally, as well as strengthening skills in dealing with various life challenges. An optimal counseling environment includes various factors that can facilitate an individual's personal growth. This article identifies some important tools that can help create a conducive environment, including: (1). A comfortable counseling room: A comfortable and safe counseling room provides an opportunity for individuals to feel calm and open while communicating with the counselor. Facilities such as comfortable furniture, good lighting, and minimal noise can enhance the effectiveness of counseling sessions. (2). Information resources: Building an optimal counseling environment involves access to relevant and up-to-date information resources. Counselors need to provide books, magazines, journals, and other reference materials related to counseling topics for individuals to expand their understanding of personal growth. (3). Supporting technology: Technological developments have opened up new opportunities in the field of counseling guidance. The utilization of software, mobile applications, and online platforms can help expand the reach of counseling guidance, facilitate accessibility, and strengthen communication between counselors and individuals in need of guidance. (4). Collaboration with related parties: Building an optimal counselling environment also involves collaborating with related parties, such as educational institutions, community organizations, and mental health institutions. This collaboration can expand the reach of counseling guidance and create synergy in facilitating individuals' personal growth. In this context, facilities and infrastructure including comfortable counseling rooms, adequate information resources, supporting technology, and collaboration with related parties are important factors in creating an environment conducive to individuals' personal growth